Double diffusion, slips and variable diffusivity effects on combined heat mass transfer with variable viscosity via a point transformation. (1st January 2013) - Ferdows, M.; Uddin, Md. J.; Khaleque, Tania S.
The present paper investigates heat and mass transfer over a moving nano-porous plate in porous media with hydrodynamic and thermal slip boundary conditions and concentrationdependent diffusivity, taking into account the Soret and Dufour effects and temperaturedependent viscosity. The similarity representation of the system of partial differential equations of the problem is obtained via point transformation. The resulting equations are solved numerically. A representative set of results for the dimensionless velocity, the dimensionless temperature and the dimensionless concentration functions is displayed to show the influence of parameters (velocity slip parameter a, thermal slip parameter γ, suction parameter Fw, concentration diffusivity parameter b, Prandtl number Pr, Schmidt number Sc, viscosity parameter θr, Soret number Sr and Dufour number Df, Darcy parameter Da and the generation parameter Q) on them.